Don't Act Baryshnikov in Beckett - Shapiro, Laura (Dance Books Ltd., Alton,Hampshire (UK), 2008)
Baryshnikov's willingness to undermine everything he does best in the name of a fresh challenge has been a hallmark of his work for three decades. When you see him onstage in the four plays that make up Beckett Shorts, it's as if you've never seen him anywhere.